Comparison of music stimuli to support mindfulness meditation - Dvorak, Abbey L; Hernandez-Ruiz, Eugenia (Psychology of music, 2021)
The purpose of this study was to compare the effectiveness of and preference for different auditory stimuli in supporting mindfulness meditation. Undergraduate non-musicians (N = 57) listened to four different auditory stimuli guiding them in a mindfulness meditation: script only (i.e., Script), steady beat (i.e., Beat), beat and harmonic progression (i.e., Harmony), and beat, harmony, and melody (i.e., Melody). This study used a within-subjects repeated-measures design with the four conditions counterbalanced and randomized across participants. Participants rated responses using the Mindful Attention Awareness Scale (MAAS), completed the Absorption in Music Scale (AIMS), and ranked auditory stimuli according to preference and usefulness for mindfulness meditation. A repeated-measures analysis of covariance (ANCOVA) on the MAAS scores, using the AIMS as a covariate, indicated no statistically significant difference between auditory stimuli. However, with the AIMS removed, the analysis revealed significant differences between stimuli, indicating that levels of absorption in music may moderate participants’ responses to auditory stimuli for mindfulness meditation. Friedman analyses of variance (ANOVAs) and post hoc analyses indicated that participant rankings of usefulness and preference were significantly different among conditions, with the Melody and Harmony conditions ranked highest.